Strategi Pemasaran Produk di Era Modern (Reinforce: Journal of Sharia Management, 2025)
This research discusses marketing strategy which is a very important part of planning for the company as a whole, especially in situations where competitors are very tight. Today's business competition is quite tight in all fields. Market conditions are increasingly competitive, especially during the Covid-19 pandemic. Therefore, it is necessary to implement a marketing strategy 4.0 using a website as a place to market their products as a very good way. This research aims to determine marketing strategies through several methods, including websites. This research uses a literature analysis research method with a qualitative approach which aims to find out, describe and explain the actual situation regarding the marketing strategy being carried out. Data collection methods use interviews, observation and documentation methods.
Keywords: strategi pemasaran; persaingan bisnis; era modern; marketing strategy; business competition; modern era